Дослідження мотиваційно-ціннісного компоненту професійної соціалізації студентів інженерних спеціальностей - Мовчан, Яна Олександрівна (Харківський національний педагогічний університет імені Г. С. Сковороди, 2016)
Досліджується мотиваційно-ціннісний компонент професійної соціалізації студентів інженерних спеціальностей. Виділено показники мотиваційно-ціннісного компоненту. Проаналізовано результати дослідження за різними рівнями прагнення майбутніх інженерів працювати за спеціальністю.

The article deals with study of motivational and value component of professional socialization of students majoring in engineering. It is given the attributes of motivational and value component. The results of study between different levels of future engineers' aspiration for work towards a qualification are shown.
Study of motivational and value component of profession-al socialization of students majoring in engineering
Keywords: мотивація; вища технічна школа; освіта; професійна діяльність; professional socialization; future engineers; motivation of professional activity; motivation of succeed; professional values